The Role of Library Facilities and Infrastructure Management in Improving Educational Services at SMKN 1 Sangatta Utara (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the role of library facilities and infrastructure management in improving educational services at SMKN 1 Sangatta Utara. In improving the quality of educational services, the existence of a well-managed library as a center for information and literacy resources is important, which supports the teaching and learning process in schools. Good management of facilities and infrastructure in the library can increase interest in visits and create a conducive learning atmosphere, which ultimately contributes to improving the quality of education. This study uses a qualitative approach with a descriptive design, which collects data through observation, interviews, and documentation at SMKN 1 Sangatta Utara. The results of the study indicate that library facilities and infrastructure management has a very important role in improving the quality of educational services in schools. Efforts made by the library to improve educational services include developing book collections that are relevant to curriculum needs and student interests as well as improving facilities and the quality of library staff. Library management involves the stages of planning, organizing, developing human resources, leadership, controlling, and maintenance to maintain smooth library management and improve the quality of services provided to students. Overall, systematic and student-oriented management has the potential to increase the role of the library as an effective and efficient learning center in supporting the educational process in schools